Noise Reduction Algorithm Based on Template Wavelet Coefficients - Bezvesilniy, O.O.; Vynogradov, V.V.; Schuenemann, K. (Радиофизика и радиоастрономия, 2000)
In the paper, a new algorithm based on the application of template wavelet coefficients is proposed to solve the problems concerning noise reduction in the vicinity of edges in signals and images and suppressing parasitic oscillations, which arise when threshold wavelet algorithms are used. It is shown that this approach calls for choosing a specific wavelet. Examples of the application of the developed technique are given. В статье предложен новый алгоритм, основанный на применении шаблонных вейвлетных коэффициентов для решения проблем, связанных с удалением шума в окрестности границ в сигналах и изображениях и подавлением паразитных осцилляций, которые возникают при использовании пороговых вейвлетных алгоритмов. Показано, что этот подход требует выбора специального вейвлета. Приведены примеры применения предложенного подхода. У статті запропоновано новий алгоритм, що базується на використанні шаблонних вейвлетних коефіцієнтів для розв’язання проблем, пов’язаних з видаленням шуму поблизу меж в сигналах та зображеннях і знищення паразитних осциляцій, що виникають у разі застосування порогових вейвлетних алгоритмів. Зазначено, що цей підхід вимагає вибору спеціального вейвлета. Наведено приклади використання запропонованого підходу.